The Influence of Work Stress, Leadership, and Compensation on Employee Performance at PT Bahana Prestasi Surabaya - Rara Puspa Kirana; Budi Prabowo (Universitas KH. Abdul Chalim Mojokerto, 2025)
Increased intense business competition encourages all industries from various sectors to create human resource management strategies to improve performance as a foundation for competing against competitors. The implementation of effective human resource management strategies can affect the improvement of employee performance so that it has an impact on organizational performance. The purpose of this research is to understand and analyze the effect of job stress, leadership and compensation on employee performance. In this research, the intended population is all employees of PT Bahana Prestasi Surabaya, using a saturated sampling technique of 54 employees as a sample. The method applied is associative research with a quantitative approach, and uses Multiple Linear Regression analysis techniques. The research results obtained simultaneously the variables of work stress, leadership, and compensation have a significant relationship to employee performance. Partial testing of work stress and leadership variables has a significant relationship to employee performance, while the compensation variable has an insignificant relationship to employee performance.